Predictors of Empathic Concern: The Roles of Compassion Fatigue and Positive Affect - Abdi, Mansour (Journal of Personality and Psychosomatic Research (JPPR), 2024)
The objective of this study was to investigate the relationships between Empathic Concern, Compassion Fatigue, and Positive Affect among professionals in caregiving roles. Specifically, it aimed to identify key predictors of empathic behavior and their impact on professional quality of life. A cross-sectional design was employed, involving 250 participants selected through stratified random sampling from various professional backgrounds. Data were collected using validated instruments: the Interpersonal Reactivity Index (IRI) for Empathic Concern, the Professional Quality of Life Scale (ProQOL) for Compassion Fatigue, and the Positive and Negative Affect Schedule (PANAS) for Positive Affect. Data analysis was conducted using SPSS-27, including Pearson correlation coefficients and multiple linear regression analysis to explore the relationships between the variables. Descriptive statistics revealed that participants had a mean Empathic Concern score of 4.35 (SD = 0.67), a mean Compassion Fatigue score of 3.12 (SD = 0.89), and a mean Positive Affect score of 3.87 (SD = 0.75). Pearson correlation analysis showed a significant negative correlation between Compassion Fatigue and Empathic Concern (r = -0.42, p = 0.001), and a significant positive correlation between Positive Affect and Empathic Concern (r = 0.56, p < 0.001). Multiple linear regression analysis indicated that Compassion Fatigue (B = -0.28, SE = 0.05, β = -0.34, t = -5.60, p = 0.001) and Positive Affect (B = 0.47, SE = 0.07, β = 0.52, t = 7.03, p < 0.001) significantly predicted Empathic Concern, accounting for 37% of the variance (R² = 0.37, F(2, 247) = 58.76, p < 0.001). The study concluded that Positive Affect significantly enhances Empathic Concern, while Compassion Fatigue reduces it. These findings suggest the importance of fostering Positive Affect and mitigating Compassion Fatigue among professionals to maintain high levels of empathy. Interventions such as mindfulness and self-compassion training may be beneficial in achieving these goals.